2023
DOI: 10.3390/su152416735
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Country Statistical Analysis Covering Turkey, Slovakia, and Romania in an Educational Framework

Tugce Pekdogan,
Mihaela Tinca Udriștioiu,
Silvia Puiu
et al.

Abstract: This paper uses hierarchical regression analysis, a statistically robust method, to explore the correlations between two meteorological parameters and three particulate matter concentrations. The dataset is provided by six sensors located in three cities from three countries, and the measurements were taken simultaneously for three months at each minute. Analyses and calculations were performed with the Statistical Package for the Social Sciences (SPSS). The results underscore that the complexity of air pollut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The distribution of sensors was strategically planned. With its higher population density and relatively few environmental monitoring stations, Adana required a denser sensor network to adequately capture spatial variability in air quality [ 45 , 46 ]. This strategic positioning allows for a more comprehensive assessment of air quality in a rapidly industrialized region experiencing significant urban growth.…”
Section: Methodsmentioning
confidence: 99%
“…The distribution of sensors was strategically planned. With its higher population density and relatively few environmental monitoring stations, Adana required a denser sensor network to adequately capture spatial variability in air quality [ 45 , 46 ]. This strategic positioning allows for a more comprehensive assessment of air quality in a rapidly industrialized region experiencing significant urban growth.…”
Section: Methodsmentioning
confidence: 99%
“…Akiner (2020) [18] addressed environmental pollution in the Mediterranean Sea along the Turkish coast, including Adana. Pekdogan et al (2023) [19] investigated particulate matter measurements in Adana, concluding that PM levels were high during the months of measurement. Consequently, air pollutants such as PM 10 , O 3 , CO, NO x , NO, NO, NO 2 , H 2 S, and SO 2 originating from high population density and industrial activities were identified in this region.…”
Section: Introductionmentioning
confidence: 99%